Direct Repair of Iatrogenic Vertebral Artery Injury Associated With Anterior Cervical Corpectomy: 2-Dimensional Operative Video. Issue 2 (19th June 2019) - Almefty, Rami O; Albuquerque, Felipe C; Spetzler, Robert F; Turner, Jay D
Abstract: Vertebral artery (VA) injury during anterior cervical spine surgery has potentially devastating neurovascular consequences. Our video highlights the operative nuances of exposing and directly repairing the V2 segment of the VA from an anterior approach. A 67-year-old woman undergoing anterior cervical corpectomy at another hospital began briskly bleeding from a suspected VA injury. Upon emergency transfer of the patient to our facility, angiography confirmed a right VA pseudoaneurysm at the level of the C5 corpectomy. The decision was made to repair the VA directly, thus avoiding vessel sacrifice and stenting. The previous anterior exposure was reopened. The longus colli was mobilized laterally on the right side to expose the C4 and C6 anterior tubercles. A plane was developed in the transverse foramina from C4 to C6, and the foramina were unroofed anteriorly using a high-speed drill and Kerrison rongeurs. The injured segment of the VA was exposed, and the platelet plug over the injured VA was identified. The proximal and distal ends of the injured segment were temporarily clipped, and the platelet plug was removed, revealing a small, ovoid-shaped' full-thickness arterial wall defect. The VA injury was repaired with simple running 10-0 nylon sutures. Indocyanine green angiography confirmed rapid filling of the patent lumen. The corpectomy and anterior fixation were completed. The patient was placed on aspirin therapy postoperatively. The patient remained neurologically intact without neurovascular sequelae at the 1-yr follow-up. The patient consented to surgical treatment (Institutional Review Board review was not necessary). Used with permission from Barrow Neurological Institute.